KONSEP KURIKULUM PENDIDIKAN ISLAM (Perbandingan antar Tokoh / Aliran) - Muhammad Muttaqin; Erik Pebrikarlepi (Lughoti (Jurnal Pendidikan Bahasa Arab) Jurnal program studi PBA, 2021)
???Humans were created as perfect beings who are different from other creatures, who are endowed with reason and thoughts by God. So that he can actualize himself as a caliph on earth. To achieve this perfection, humans must go through various processes. One of them is education. Islamic education which philosophizes Al Quran and Al Hadith. In every case or achievement of goals, of course, requires careful planning, as well as in the world of education. Educational goals will be achieved when there is a planning process to achieve them. In the world of education, the planned program is called the educational curriculum???. Key Words : The Concept Of Islamic Education Curriculum